Micro-brushing-based technique to gain fresh urothelial cells for gene expression analysis - Kuhn, Christoph; Lehmann, Marie-Louise (Journal of toxicology and environmental health. Part A, 2017)
The gold standard of saving fresh tissue in liquid nitrogen has some serious disadvantages in that this process is not available in daily medical routine practices even in many tumor centers. Our approach of a new minimally invasive technique is obtaining urothelial cells via micro-brushing the urinary bladder on the occasion of urological routine methods such as transurethral resection (TUR). Urothelial cells were obtained from 25 patients via two different micro-brushes from tumor tissue and from macroscopically healthy tissue during TUR. These cells were immediately transferred into RNA stabilization reagent and stored at −20°C. Later, mRNA was isolated, transcribed into cDNA, and amplified. cDNA was stored at −20°C until analysis. The mean RNA quantity was 99.5 ng/μl from tumor tissues and 66.3 ng/μl from macroscopically tumor-free tissue, enabling a considerable number of analyses. The quality of the gained cDNA allowed semi-quantitative PCR analysis of GSTM1 expression as well as quantitative PCR analysis of c-Myc expression. The new technique presents several important advantages. First, staging and grading of the stained tumor sample can be examined immediately, whereas fresh frozen sample is not examined until some days later. Further, this method can be applied in hospitals with no access to liquid nitrogen or without capability to provide an additional examination of frozen tumor sample by a pathologist. This presented minimally invasive method enables investigation of gene expression in the urinary bladder without disadvantages of the need for storage of fresh tissues in liquid nitrogen.
Gesehen am 26.11.2018